IMPLEMENTATION THE GOOD GOVERNANCE PRINCIPLES IN THE PUBLIC ADMINISTRATION SYSTEM - Telychkan, Yuriy (Theory and Practice of Public Administration, 2019)
establishment of principles by which the creation of laws, theories, and their practical application is possible. The article analyzes the published research on defining and forming the principles system of public administration. The purpose of this article is to identify tools for implementing the principles of good governance in the public administration and administration system, in particular: fair elections, representation and participation; feedback; efficiency and effectiveness; openness and transparency; rule of law; ethical behavior; competence and ability; innovation and openness to change; sustainable development and strategic orientation; sound financial management; human rights, cultural diversity and social cohesion; accountability. The article paralyzes the transition from governance to public administration through the implementation the principles of good governance. It was noted that in order to facilitate the fuller implementation the principles of good governance and to enable them to monitor the state of their implementation, the Council of Europe has developed and proposed: the constituents of the principle (a description of the activities enabling the provisions of each principle to be more fully implemented), indicators (to assess the degree of implementation the constituents of the principle best practices currently available), questionnaires (to measure indicator values). It is established that in Europe today the principles of good governance are the basis of a new paradigm of public administration, which has taken all the best, the most effective from the previous theoretical and practical achievements of democratic reforms in European countries.